A twin study exploring the association between childhood emotional and behaviour problems and specific psychotic experiences in a community sample of adolescents. (3rd November 2017) - Shakoor, Sania; McGuire, Philip; Cardno, Alastair G.; Freeman, Daniel; Ronald, Angelica
Abstract : Background: Childhood emotional and behaviour problems are antecedents for later psychopathology. This study investigated genetic and environmental influences shaping the longitudinal association between childhood emotional and behaviour problems and specific PEs. Method: In a community‐based twin sample, parents reported on emotional and behaviour problems when twins were ages 7 and 12 years. At age 16 years, specific PEs were measured using self‐reports and parent reports. Structural equation model‐fitting was conducted. Results: Childhood emotional and behaviour problems were significantly associated with paranoia, cognitive disorganisation and parent‐rated negative symptoms in adolescence (mean r = .15–.38), and to a lesser extent with hallucinations, grandiosity and anhedonia (mean r = .04‐.12). Genetic influences on childhood emotional and behaviour problems explained significant proportions of variance in adolescent paranoia (4%), cognitive disorganisation (8%) and parent‐rated negative symptoms (3%). Unique environmental influences on childhood emotional and behaviour problems explained ≤1% of variance in PEs. Common environmental influences were only relevant for the relationship between childhood emotional and behaviour problems and parent‐rated negative symptoms (explaining 28% of variance) and are partly due to correlated rater effects. Conclusions: Childhood emotional and behaviour problems are significantly, if weakly, associated with adolescent PEs. These associations are driven in part by common genetic influences underlying both emotional and behaviour problems and PEs. However, psychotic experiences in adolescence are largely influenced by genetic and environmental factors that are independent of general childhood emotional and behaviour problems, suggesting they are not merely an extension of childhood emotional and behaviour problems.